Stem cell recruitment, angiogenesis, and tissue regeneration in substance P-conjugated poly(l-lactide-co--caprolactone) nonwoven meshes - Shafiq, Muhammad; Jung, Youngmee; Kim, Soo Hyun (WILEY, 2015)
Recruitment of endogenous stem cells to impaired tissues holds enormous potential to regenerative medicine. In this study, we examined whether covalently conjugated substance P (SP) would significantly enhance the recruitment of stem cells and promote angiogenesis in poly(l-lactide-co-epsilon-caprolactone) (P(LA-co-CL)) meshes. SP was conjugated with star-shaped P(LA-co-CL) copolymer using carbonyldiimidazole chemistry. P(LA-co-CL) and SP-conjugated star-shaped P(LA-co-CL) copolymers were mixed in appropriate proportions and electrospun to fabricate nonwoven meshes. Amino acid analysis confirmed the conjugation of SP with star-shaped P(LA-co-CL) copolymers. Conjugated SP remained bioactive and recruited human bone-marrow-derived mesenchymal stem cells in an in vitro transwell migration assay. Moreover, SP was released in a sustained fashion from the nonwoven meshes for up to 30 days. P(LA-co-CL) as well as SP containing meshes were implanted subcutaneously in Sprague-Dawley rats (n=16) for 14 and 21 days. Hematoxylin and eosin staining of the retrieved samples revealed cellularization of P(LA-co-CL) as well as SP containing meshes. Large and mature blood vessels were observed in greater numbers in SP-containing meshes compared with their control counterparts as revealed by Masson's trichrome staining. We also observed a larger number of von Willebrand factor-positive vessels in SP-containing meshes than in the controls. Significantly large numbers of CD29- and CD90-positive stem cells were recruited in the meshes containing SP. Collectively, these findings suggest that the methodology presented may have broad applications in regenerative medicine, and these novel scaffolding materials can be used for in situ tissue regeneration of soft tissues. (c) 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2673-2688, 2015.
Keywords: EPIDERMAL-GROWTH-FACTOR; IN-VIVO; POLY(LACTIC ACID-CO-LYSINE); PROGENITOR CELLS; VASCULAR GRAFTS; PEPTIDE; SCAFFOLDS; DELIVERY; DIFFERENTIATION; BIOMATERIALS